Effects of kidney perfusion on renal stiffness and tissue fluidity measured with tomoelastography in an MRI-compatible ex vivo model - Castelein, Johannes; Pamplona, Carolina; Armstrong Junior, Roberto; Vidal dos Santos, Marina; Sack, Ingolf; Dierckx, Rudi; Moers, Cyril; Borra, Ronald (Frontiers in Bioengineering and Biotechnology, 2023)
Stiffness plays a vital role in diagnosing renal fibrosis. However, perfusion influences renal stiffness in various chronic kidney diseases. Therefore, we aimed to characterize the effect of tissue perfusion on renal stiffness and tissue fluidity measured by tomoelastography based on multifrequency magnetic resonance elastography in an ex vivo model. Five porcine kidneys were perfused ex vivo in an MRI-compatible normothermic machine perfusion setup with adjusted blood pressure in the 50/10 – 160/120 mmHg range. Simultaneously, renal cortical and medullary stiffness and fluidity were obtained by tomoelastography. For the cortex, a statistically significant (p < 0.001) strong positive correlation was observed between both perfusion parameters (blood pressure and resulting flow) and stiffness (r = 0.95, 0.91), as well as fluidity (r = 0.96, 0.92). For the medulla, such significant (p < 0.001) correlations were solely observed between the perfusion parameters and stiffness (r = 0.88, 0.71). Our findings demonstrate a strong perfusion dependency of renal stiffness and fluidity in an ex vivo setup. Moreover, changes in perfusion are rapidly followed by changes in renal mechanical properties – highlighting the sensitivity of tomoelastography to fluid pressure and the potential need for correcting mechanics-derived imaging biomarkers when addressing solid structures in renal tissue.